A SPEECH ACT ANALYSIS: TEACHERS’ ILLOCUTIONARY ACTS IN HAPPY ENGLISH COURSE 2 - Evi Isfiatul Jannah; Fajar El Fikri; Iwan Setiawan; Abdul Hakim; Irma Khoirot Daulay (Institut Pendidikan Tapanuli Selatan, 2024)
Communication is important because it provide the element to perform an effective interaction in teaching and learning process. When the teacher makes an utterance, it could be called as speech acts. The teacher’s speech act in English classroom plays an important role in facilitating the effective interaction in a communication with the students. All of the teachers use speech acts to express their action to know how the students conclude the intended meaning of what the teachers said. The purposes of this research are analyzed and compared the two teachers’ speech based on the forms of speech acts in Searle’s illocutionary act theory. This research will focus on the utterances of the English teachers in Happy English Course 2 Pare, Kediri. In this research, the researchers used qualitative research design, specifically in case study. The research result showed that the teachers tend to use directive acts form in teaching and assertive acts form in announcing a thing. These results are aligned with previous researches who suggested the use of directive speech acts to emphasize the awareness of teachers regarding their position of authority and ability to efficiently manage their classroom environment, and develop the students’ communicative competence